Understanding human-centred artificial intelligence in the banking sector - OBUCHETTIAR, Krishnaraj Arul (Institutional Knowledge at Singapore Management University, 2023)
The advent of smart digital devices and social media has shaped how consumers interact and transact with their financial institutions. Consumers increasingly want hyperpersonalised interactions that are more frequent and proactive, while financial institutions have a growing need to cater to consumers’ new demands. Financial institutions, such as banks, continuously adapt to the latest technologies to keep pace with evolving customer behaviours, needs, and experiences. One such emerging technology is artificial intelligence (AI). Many organisations realise the potential of AI; however, a human-centred AI system must be capable of understanding human characteristics and making decisions like humans. This paper presents an empirical study, involving survey participants from three different groups: banks, IT vendors and focus groups. Emphasis is placed on understanding the effect of practising a co-development mindset between these three key stakeholder groups on the outcome of developed human-centred AI-enabled products and services. The survey results show that capturing and processing human emotions (HE) to train an AI model improves customer experience and trustworthiness, and a co-development mindset practised between the IT vendor and the bank will positively influence the effectiveness of human-centred AI-enabled products and services.